Study of influence of boron, aluminum, manganese, silicon and RZM on wear resistance of cast materials - N. F. Nevar; Ju. N. Fasevich (Литьë и металлургия, 2003)
In the offered work there have been carried out the wear resistant tests of the cast materials experimental samples in conditions of friction at contact with steel and abrasive riders, conjugated with impingement attacks.